Riboflavin- and chlorophyllin-based antimicrobial photoinactivation of Brevundimonas sp. ESA1 biofilms - Gricajeva, Alisa; Buchovec, Irina; Kalėdienė, Lilija; Badokas, Kazimieras; Vitta, Pranciškus (Frontiers in Cellular and Infection Microbiology, 2022)
Some Brevundimonas spp. are globally emerging opportunistic pathogens that can be dangerous to individuals with underlying medical conditions and for those who are immunocompromised. Gram-negative Brevundimonas spp. can form resilient sessile biofilms and are found not only in different confined terrestrial settings (e.g., hospitals) but are also frequently detected in spacecraft which is inhabited by astronauts that can have altered immunity. Therefore, Brevundimonas spp. pose a serious health hazard in different environments, especially in its biofilm form. Conventional antimicrobials applied to disrupt, inactivate, or prevent biofilm formation have limited efficiency and applicability in different closed-loop systems. Therefore, new, effective, and safe biofilm control technologies are in high demand. The present work aimed to investigate antimicrobial photoinactivation (API) of Brevundimonas sp. ESA1 monocultural biofilms mediated by non-toxic, natural photosensitizers such as riboflavin (RF) and chlorophyllin (Chl) with an emphasis of this technology as an example to be safely used in closed-loop systems such as spacecraft. The present study showed that Chl-based API had a bactericidal effect on Brevundimonas sp. ESA1 biofilms at twice the lower irradiation doses than was needed when applying RF-based API. Long-term API based on RF and Chl using 450 nm low irradiance plate has also been studied in this work as a more practically applicable API method. The ability of Brevundimonas sp. ESA1 biofilms to reduce alamarBlue™ and regrowth analysis have revealed that after the applied photoinactivation, bacteria can enter a viable but non-culturable state with no ability to resuscitate in some cases.